PERAN KELUARGA DALAM PENDIDIKAN IMAN REMAJA KATOLIK DI TENGAH KEMAJUAN TEKNOLOGI - Agatatea, Fantasi; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This study aims to analyze the role of Catholic families in the faith education of teenagers, especially in the midst of current technological advancements. It is hoped, that this research can provide benefits and serve as a source of information regarding the role of families in the faith education of teenagers amidst technological advancements. The method used in this research is qualitative method with interview techniques. The informants in this study amounted to seven (7) people, namely several Catholic families in the Santa Cecilia Community, specifically in the area 4th, Parish of Saint Cornelius, Madiun. The informants in this study are several Catholic families who have children in the teenage age range of 12-18 years old. The results of this study indicate that parents have played an active role in providing religious education to teenage children by teaching them to pray, setting a good example, showing love and affection, and involving teenagers in church life